Post-Traumatic Stress among Evacuees from the 2016 Fort McMurray Wildfires: Exploration of Psychological and Sleep Symptoms Three Months after the Evacuation - Genevieve Belleville (International Journal of Environmental Research and Public Health, 2019)
This study documents post-traumatic stress symptoms after the May 2016 wildfires in Fort McMurray (Alberta, Canada). A sample of 379 evacuees completed an online questionnaire from July to September 2016, and a subsample of 55 completed a psychiatric/psychological diagnostic interview. According to a self-report questionnaire, 62.5% of respondents had a provisional post-traumatic stress disorder (PTSD). The interview confirmed that 29.1% met criteria for PTSD, 25.5% for depression, and 43.6% for insomnia; in most cases, insomnia was definitely or probably related to the fires. Traumatic exposure may elicit or exacerbate sleep problems, which are closely associated with PTSD after a disaster.